PENGEMBANGAN MEDIA PEMBELAJARAN FLASH CARD MATHEMATICS PADA PEMBELAJARAN MATEMATIKA - Rahel Wiwit; M. Jainuri; Sugeng Riyadi (Mat-Edukasia, 2021)
The purpose of this research is to instructional media for flash card mathematics for class VII SMP/MTs. is valid, practical and effective. This research uses a research and development (R&D) method. Media characteristics flash card mathematics concrete, clarifies a problem, easy to use and has a special characteristic. Intructinal media flash card validated by 5 expert of material, language and media. The validity of the product is know from the validation sheet. The practicality of the product is know from the practicality questionnaire sheet and student interviews. Effectiveness is know from the activity sheet and student learning outcomes. The average score of the validation result of the material expert is 4,46 with a very valid category, a language expert is 3,90 with very valid category, a media expert is 4,81 with very valid category, a teacher expert is 4,24 with very valid category and overall validation is 3,53 with very valid category. The percentage of practicality questionnaire responses was 80,01% with very practical category. The average percentage of activities was 87,57% with very effective category and the percentage of student learning outcomes 81,80% with effective category. Based on this result the research and development has been valid, practical and effective